Peran Guru Pendidikan Agama Islam Untuk Mengatasi Perilaku Bullying Pada Siswa Kelas VIII di SMPN 3 Satu Atap Karangsambung Kebumen - Sodiq, Fathus; Eliyanto, Eliyanto (IAINU Kebumen, 2024)
The objectives of this study are: (1) to determine the role of Islamic Religious Education teachers in overcoming bullying behavior in class VIII students at SMPN 3 Satu Atap Karangsambung Kebumen. (2) to determine the forms of bullying experienced by class VIII students at SMPN 3 Satu Atap Karangsambung Kebumen. (3) to determine the factors causing bullying carried out by class VIII students at SMPN 3 Satu Atap Karangsambung Kebumen. This study adopted a qualitative approach using data collection techniques through observation, interviews, and documentation. The subjects of the study consisted of the Principal, Islamic Religious Education teachers, and class VIII students at SMPN 3 Satu Atap Karangsambung Kebumen. Data analysis was carried out using condensation techniques, data presentation, as well as drawing conclusions and verification. The results of this study indicate that: (1) the role of teachers is very vital in overcoming bullying, by training students to have good knowledge, skills, and morals. Teachers function as educators who provide advice and sanctions for bad behavior, as role models who maintain behavior and provide positive examples, and as guides who provide direction in learning and school activities. (2) The forms of bullying that occur at SMPN 3 Satu Atap Karangsambung include pinching friends, making fun of them, isolating them, and taunting them. (3) The factors causing bullying consist of individual, school, and social environment factors.